Tuberculous pleurisy drives marked effector responses of γδ, CD4+, and CD8+ T cell subpopulations in humans. Issue 5 (8th July 2015) - Zeng, Jincheng; Song, Zeqing; Cai, Xiaozhen; Huang, Su; Wang, Wandang; Zhu, Yanfen; Huang, Yinan; Kong, Bin; Xiang, Wenyu; Lin, Dongzi; Liu, Ganbin; Zhang, Junai; et al.
Abstract : Over‐reactive effector responses of γδ T and αβ T cells, and their interrelation with Foxp3 + Treg in pleural and other compartments. Abstract : Although tuberculous pleurisy (TP) presumably involves a hypersensitivity reaction, there is limited evidence indicating overreactive effector responses of γδ T cells and αβ T cells and their interrelation with Foxp3 + Tregs in pleural and other compartments. We found that TP induced reciprocal representations of Foxp3 + Tregs and Mtb phosphoantigen‐specific Vγ2Vδ2 T cells in different anatomic compartments. Patients with TP exhibited appreciable numbers of "proliferating" Ki‐67 + Vγ2Vδ2 T cells in the airway where Foxp3 + Tregs were not dominant, whereas striking increases in Foxp3 + Tregs in the blood and pleural compartments coincided with low frequencies of Vγ2Vδ2 T cells. Interestingly, anti‐tuberculosis chemotherapy control of Mtb infection in patients with TP reversed reciprocal representations of Foxp3 + Tregs and proliferating Vγ2Vδ2 T cells. Surprisingly, despite high‐level Foxp3 + Tregs, TP appeared to drive overreactive responses of IFN‐γ‐producing Vγ2Vδ2, CD4 + CD25 +, and CD8 + CD25 + T effector subpopulations, whereas IL‐22‐producing Vγ2Vδ2 T cells increased subtly. Th1 effector responses were sustained despite remarkable declines in Foxp3 + Tregs at 1 mo after the treatment. Overreactive T effector responses of Mtb‐reactive γδ T cells, αβ CD25 + CD4 +, and CD25 + CD8 + T cell subpopulations appear to be immune features for TP. Increased Foxp3 + Tregs might be responsive to overreactive TP but unable to influence T effector responses despite having an inverse relation with proliferating Vγ2Vδ2 T cells.